α-Glucosidase inhibitory activity of polyphenol-rich sugarcane extract: screening and mechanistic insights based on biolayer interferometry-mass spectrometry - Yao, Mengli; Liu, Jia; Zhou, Fang; Li, Haizhi; Wang, Ruoyong; Han, Zhong; Liu, Jie; Chen, Wei; Liu, Guoyu; Yang, Shuheng; Duan, Shenlin; Han, Xiaofeng; et al. (Frontiers in Nutrition, 2025)
IntroductionPolyphenol-rich sugarcane extract (PRSE) contains bioactive compounds with potential hypoglycemic properties, but its direct interaction with α-glucosidase has not been explored.MethodsThis study investigated the inhibitory mechanism of PRSE on α-glucosidase using enzyme kinetics. Bioactive compounds with α-glucosidase-binding affinity were identified through biolayer interferometry-mass spectrometry (BLI-MS), and the binding mechanisms were further explored via molecular docking analysis.Results and discussionPRSE was found to inhibit α-glucosidase through a mixed-type mechanism. A total of 29 compounds, including 4 coumarins, 9 phenolic acids, and 16 flavonoids, were identified in the PRSE dissociation solution. Representative compounds included coumarin, kaempferol, apigenin 7-o-neohesperidoside, and vicenin 3. Notably, apigenin 7-o-neohesperidoside and vicenin 3 were identified for the first time as potential α-glucosidase inhibitors.These compounds interacted with key residues of α-glucosidase, such as Asp and Glu, via hydrogen bonding, π-anion interactions, and hydrophobic forces. These findings suggest that PRSE could serve as a promising natural source of α-glucosidase inhibitors. The application of BLI-MS proved effective for screening target bioactive compounds in plant extracts. PRSE may have potential applications in functional foods for postprandial glycemic control and type 2 diabetes prevention.